2019
DOI: 10.3892/etm.2019.7671
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NKILA was upregulated in diabetic cardiomyopathy with early prediction values

Abstract: Nuclear factor-κB interacting long non-coding RNA (LncRNA NKILA) is a well-studied tumor suppressor lncRNA in several types of malignancies. The present study reports the involvement of this lncRNA in diabetic cardiomyopathy (DC). A 8-year-follow-up study on 312 diabetic patients without exhibiting obvious complications demonstrated that plasma lncRNA NKILA levels were upregulated specifically in diabetic patients who developed DC but not in patients with other complications. Plasma levels of lncRNA NKILA at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…A study by Li et al in 2019 27 demonstrated that lncRNA NKILA was specifically upregulated in patients with T2DM who later developed diabetic-related complications such as cardiomyopathy, suggesting that overexpression of the lncRNA NKILA may contribute to cardiomyocyte apoptosis and its involvement in the progression of diabetic cardiomyopathy (DC). It was suggested that suppressing expression of the lncRNA NKILA may inhibit the development of DC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Li et al in 2019 27 demonstrated that lncRNA NKILA was specifically upregulated in patients with T2DM who later developed diabetic-related complications such as cardiomyopathy, suggesting that overexpression of the lncRNA NKILA may contribute to cardiomyocyte apoptosis and its involvement in the progression of diabetic cardiomyopathy (DC). It was suggested that suppressing expression of the lncRNA NKILA may inhibit the development of DC.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that suppressing expression of the lncRNA NKILA may inhibit the development of DC. 27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the specific intrinsic mechanism had not been fully elucidated, studies have confirmed that NKILA played an important role in inflammation. For instance, Li et al presented NKILA was up-regulated in diabetic cardiomyopathy and could restrain cell apoptosis [25]. Zhu et al presented NKILA played a proinflammatory response role in endothelium inflammation [26].…”
Section: Discussionmentioning
confidence: 99%